Reader Response: Spontaneous ARIA-like Events in Cerebral Amyloid Angiopathy–Related Inflammation: A Multicenter Prospective Longitudinal Cohort Study. (18th October 2022) - Filippi, Massimo; Cecchetti, Giordano; Spinelli, Edoardo Gioele; Agosta, Federica
Abstract : In a multicenter prospective study, Antolini et al. 1 offered critical information on the natural history and treatment outcomes of spontaneous amyloid-related imaging abnormality (ARIA)–like events in a large cohort of inpatients diagnosed with cerebral amyloid angiopathy–related inflammation (CAA-ri). We appreciate the authors' comments on the overlap in neuroradiologic features and main pathogenic contributors to both ARIA and ARIA-like events. Considering the yet unanswered issues regarding the management of drug-induced ARIAs in a real-world setting, 2 this study provides reasonable indications. Because only anecdotal evidence has suggested the use of corticosteroids to facilitate resolution of symptomatic extensive ARIAs, 3 here, the authors suggested that intravenous corticosteroid pulse therapy, followed by slow oral tapering might guarantee better long-term outcomes. Moreover, natural β-amyloid–targeting autoantibodies in the CSF, which characterize CAA-ri (with or without co-occurrent AD), 4 may meet the specific requirement of biomarkers to assess the individual risk for ARIA development. Therefore, monitoring levels of β-amyloid–targeting antibodies, both therapeutically administered and naturally produced, can be suggested as a strategy to tailor treatment individually, maintaining a "therapeutic window" for the safe clearance of β-amyloid through vascular spaces and minimizing the occurrence of ARIAs. 5